Towards De-Implementation of low-value thyroid care in older adults. Issue 5 (22nd October 2022) - Perkins, Jennifer M.; Papaleontiou, Maria
Abstract : Purpose of review: This review discusses the current literature regarding low-value thyroid care in older adults, summarizing recent findings pertaining to screening for thyroid dysfunction and management of hypothyroidism, thyroid nodules and low-risk differentiated thyroid cancer. Recent findings: Despite a shift to a "less is more" paradigm for clinical thyroid care in older adults in recent years, current studies demonstrate that low-value care practices are still prevalent. Ineffective and potentially harmful services, such as routine treatment of subclinical hypothyroidism which can lead to overtreatment with thyroid hormone, inappropriate use of thyroid ultrasound, blanket fine needle aspiration biopsies of thyroid nodules, and more aggressive approaches to low-risk differentiated thyroid cancers, have been shown to contribute to adverse effects, particularly in comorbid older adults. Summary: Low-value thyroid care is common in older adults and can trigger a cascade of overdiagnosis and overtreatment leading to patient harm and increased healthcare costs, highlighting the urgent need for de-implementation efforts.